Social media for collaborative learning - Nur Shamsiah Abdul Rahman; Lina Handayani; Mohd Shahizan Othman; Waleed Mugahed Al-Rahmi; Shahreen Kasim; Tole Sutikno (International Journal of Electrical and Computer Engineering (IJECE), 2020)
Research on the field of using social media has gained more importance in the recent days due to the rapid development of social media technologies. Looking at the behavioral intention and attitude of using social media for collaborative learning within Malaysian higher educational institutions and the influencing factors in this regard has received little attention by researchers. The study aims at examining the determinants that affect learners’ attitude and behavior intention regarding their use social media to achieve collaborative learning. Such examination is carried out by using the Theory Acceptance Model (TAM) and Unified Theory of Acceptance and Usage of Technology (UTAUT). A total of 243 participants were recruited for this study. The findings indicated that students’ attitudes and behavior are strong indicators of their intentions in terms of using social media in collaborative learning.